New Challenges and Advances in Systems Engineering at French Universities. Issue 4 (12th January 2022) - Gouyon, David; Panetto, Hervé
ABSTRACT: This special issue of INSIGHT highlights the ninth edition of the French Systems Engineering Academia‐Industry meetings, organized by AFIS (Association Française d'Ingénierie Système), the French chapter of INCOSE, and supported by French universities as a regular series, usually every two years. Due to the COVID‐19 crisis, this edition occurred virtually in December 2020. These meetings, which are composed of workshops and plenary lectures, provides the opportunity for both academics and industrials to: debate on systems engineering practices, education, and competences development for professional situations, and develop and promote research in systems engineering.